PROGRAM KEBERSIHAN LINGKUNGAN SEKOLAH DAN KESADARAN HIDUP SEHAT DI SD SWASTA PKMI TELUKDALAM - Gaurifa, Midarwati (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The "School Environmental Cleanliness and Healthy Living Awareness Program" at SD Swasta PKMI Telukdalam aims to enhance students’ awareness of the importance of maintaining a clean environment and adopting a healthy lifestyle. This initiative involves students, teachers, and parents in a series of activities, including socialization, training, and environmental clean-up actions. Through a participatory approach, students actively engage in planning and executing activities, thereby fostering a sense of responsibility for cleanliness. Additionally, the program includes education on healthy eating habits and the importance of physical activity, implemented through various sports and educational activities. The results of the program indicate an increase in students’ awareness and participation in maintaining environmental cleanliness, as well as the adoption of healthy lifestyle practices in their daily lives. Consequently, this program not only creates a cleaner and healthier learning environment but also contributes to the development of students’ character, making them more caring towards health and the environment. The success of this program is expected to serve as a model for other schools to integrate the values of cleanliness and health into education.